An alternative plant for sustainable future: some biochemical properties of watercress (Nasturtium officinale R.Br.) - Bulut, Hilal; Yilmaz, Serdar Murat (Walter de Gruyter Gmbh, 2025)
Watercress, a semi-aquatic plant with high nutritional value, is a member of the Brassicaceae family. It is widely distributed in wetlands in Turkey and grows in or around water. This study aimed to determine some biochemical properties of Nasturtium officinale grown in eastern Turkey, such as fatty acids, lipophilic vitamins, and phytosterols. In this context, plant collected from a predetermined area were separated into roots, stems, and leaves after the washing process in the autumn of 2023. Chemical characterisation was determined by techniques such as gas chromatography for fatty acids and HPLC for vitamins and sterols. The importance of the components contained in the plant was revealed by evaluating the results obtained in the light of the literature. These results show that linolenic acid (C18:n3 LNA) was found to be present in the root at a rate of 22.71% and in the leaf at a rate of 42.45%. Palmitic acid (C16:0) was found in the stem at a rate of 17.73%. The lipophilic vitamin analysis of watercress revealed the presence of vitamins K1, K2, D2, D3, delta-tocopherol, alpha-tocopherol, ergosterol, sterol, beta-sitosterol, retinol, and retinol acetate. It was determined that ergosterol had the highest value in the leaf part (416.5 mg/g-1).
Keywords: Nasturtium officinale; fatty acid; lipophilic vitamin; phytosterol; T & uuml;rkiye